Glycemic control, periodontal disease, and tooth mobility in type 2 diabetes - Molek, Molek; Tarigan, Susiani; Nuari, Arifah Nur Amaliyah (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Diabetes mellitus, a growing global and national health crisis, is associated with various systemic complications, including often-overlooked oral health deterioration, particularly periodontal disease. While the general bidirectional link between diabetes and periodontal disease is established, research on the direct correlation between glycaemic control (HbA1c) and periodontal status or tooth mobility in specific regional contexts like Indonesia remains inconsistent. This study aimed to analyse this relationship in patients with Type 2 Diabetes Mellitus (T2DM) at Dr. Yuliddin Away Tapaktuan Hospital. An analytical survey with a cross-sectional design was conducted in September-October 2024 at RSUD dr. Yuliddin Away Tapaktuan. A convenience sample of 40 T2DM patients was selected from a population of 63. HbA1c level was the independent variable, while periodontal disease status and tooth mobility degree were the dependent variables. Data were collected via direct oral examination and patient medical records, and subsequently analysed to determine associations. The study cohort (n=40) was predominantly female (72.5%) and over 45 years old (85%). A significant majority (80.0%) exhibited uncontrolled HbA1c levels. Periodontal disease was highly prevalent, with 80.0% of patients having gingivitis. The bivariate analysis revealed a strong and statistically significant relationship between blood glucose control and periodontal disease severity (p < 0.001). Among patients with controlled HbA1c, 87.5% maintained healthy periodontal status, whereas 96.8% of those with uncontrolled HbA1c presented with gingivitis. Conversely, while all controlled HbA1c patients showed no tooth mobility (Degree 0), 21.9% of the uncontrolled group had some degree of mobility (Degree 1 or 2). However, this association between HbA1c control and tooth mobility was not statistically significant (p = 0.910). This study confirms a significant inverse relationship between optimal blood glucose control and the severity of periodontal disease in T2DM patients, particularly regarding gingivitis. Effective glycaemic management is therefore critical for promoting periodontal health. While a trend was observed, the relationship between HbA1c control and tooth mobility did not reach statistical significance, suggesting its multifactorial nature. These findings underscore the importance of integrating comprehensive diabetes management with oral healthcare to prevent and mitigate periodontal complications.